Empowering the Young towards Fullness of Life - Aerthayil, Pradeep (Journal of Dharma, 2006)
Jerome Vallabaraj, Empowering the Young towards Fullness of Life, Bangalore: Kristu Jyoti Publications, 2003, Pages 267, ISBN: 81-87370-19X.